Proactive Leadership and Structured Safety Practices: Enhancing Occupational Health and Safety Performance Through Management Involvement - Sanctis, Manoj Antony (Digital Repository of Theses - SSBM Geneva, 2025)
Occupational health and safety are pivotal in maintaining a sustainable and productive work environment. It is also no longer viewed as a back-office compliance activity but also a critical pillar in strategic management of modern enterprises. This dissertation investigates the role of how proactive leadership, managerial accountability, and structured workplace safety protocols collectively shape the organizational performance and employee well-being. The study employed a quantitative cross-sectional survey design, collecting data from 250 participants representing various designations, industries, and experience levels. A structured questionnaire comprising 26 health and safety statements was used to assess two key dimensions of health and safety management and practices. Findings highlight a significant alignment between high-performing organizations and those that embed safety into their operational standards. The study identifies consistent trends where strong executive oversight, workforce participation in safety governance, and investments in training and emergency preparedness directly contribute to reduced incident rates, enhanced workforce morale, and improved productivity. Through descriptive statistics, ANOVA, and correlation analysis, the research confirms the hypothesis that management-driven OHS integration yields measurable business value. This research not only contributes to academic literature on occupational health and safety management systems (OHSMS) but also provides a practical blueprint for executives aiming to align workplace safety with corporate objectives, risk mitigation strategies, and sustainable development goals. In an era of heightened ESG expectations and regulatory surveillance, the study underscores the competitive advantage gained by organizations that treat OHS as a core business function rather than a statutory obligation.